PD‐L1 expression enhancement by infiltrating macrophage‐derived tumor necrosis factor‐α leads to poor pancreatic cancer prognosis. Issue 1 (14th December 2018) - Tsukamoto, Masayo; Imai, Katsunori; Ishimoto, Takatsugu; Komohara, Yoshihiro; Yamashita, Yo‐ichi; Nakagawa, Shigeki; Umezaki, Naoki; Yamao, Takanobu; Kitano, Yuki; Miyata, Tatsunori; Arima, Kota; Okabe, Hirohisa; et al.
Abstract : Immunotherapy using anti‐PD‐1/PD‐L1 antibodies for several types of cancer has received considerable attention in recent decades. However, the molecular mechanism underlying PD‐L1 expression in pancreatic ductal adenocarcinoma (PDAC) cells has not been clearly elucidated. We investigated the clinical significance and regulatory mechanism of PD‐L1 expression in PDAC cells. Among the various cytokines tested, tumor necrosis factor (TNF)‐α upregulated PD‐L1 expression in PDAC cells through NF‐κB signaling. The induction of PD‐L1 expression was also caused by co‐culture with activated macrophages, and the upregulation was inhibited by neutralization with anti‐TNF‐α antibody after co‐culture with activated macrophages. PD‐L1 expression in PDAC cells was positively correlated with macrophage infiltration in tumor stroma of human PDAC tissues. In addition, survival analysis revealed that high PD‐L1 expression was significantly associated with poor prognosis in 235 PDAC patients and especially in patients harboring high CD8‐positive T‐cell infiltration. These findings indicate that tumor‐infiltrating macrophage‐derived TNF‐α could be a potential therapeutic target for PDAC. Abstract : Survival analysis revealed that PD‐L1 expression was significantly associated with poor prognosis in PDAC patients and especially in patients harboring high CD8‐positive T‐cell infiltration. The induction of PD‐L1 expression was caused by co‐culture with activated macrophages, and the upregulation was inhibited by neutralization with anti‐TNF‐α antibody after co‐culture with activated macrophages.